Anti-Toxoplasma gondii activity of Trametes versicolor (Turkey tail) mushroom extract - Homa Nath Sharma; Jonathan Catrett; Ogechi Destiny Nwokeocha; Melissa Boersma; Michael E. Miller; Audrey Napier; Boakai K. Robertson; Daniel A. Abugri (Scientific Reports, 2023)
Abstract Toxoplasma gondii (T. gondii) infection continues to rise globally in humans and animals with high socioeconomic and public health challenges. Current medications used against T. gondii infection are limited in efficacy, safety, and affordability. This research was conducted to assess the higher fungi extract effect on T. gondii tachyzoites growth in vitro and possibly decipher its mechanism of action. Furthermore, we evaluated the extract's effect on human foreskin fibroblast viability. The methanol extracts of Turkey tail (TT) mushroom was tested against T. gondii tachyzoites growth using an RH-RFP type I strain that expresses red fluorescent protein throughout culture in a dose-dependent manner using a fluorescent plate reader. Similarly, we tested the effect of the extract on host cell viability. We observed that TT extract inhibited tachyzoites growth with a 50% minimum inhibitory concentration (IC50s), IC50 = 5.98 ± 1.22 µg/mL, and 50% cytotoxic concentration (CC50s), CC50 ≥ 100 µg/mL. It was discovered that TT extract induced strong mitochondria superoxide and  reactive oxygen species production and disrupted mitochondria membrane potential in T. gondii tachyzoites. Additionally, scanning electron microscopy depicted that TT extract and pyrimethamine (PY) caused a morphological deformation of tachyzoites in vitro. In conclusion, TT methanol extract made up of phytosterols, bioactive sphingolipids, peptides, phenolic acids, and lactones could be a promising source of new compounds for the future development of anti-Toxoplasma gondii drugs. Extracts were non-cytotoxic, even at higher concentrations.